THE TEACHERS' CLINIC. - Kaulback, Frank S.; Scovill, H. T.; Gellein, Oscar S. (The Accounting Review, 1951)
Abstract This article analysis a questionnaire sent to 1000 alumni of the University of Illinois, College of Commerce. The question as presented to the alumni on this topic was adopted from one of similar type and purpose drafted by the American Council on Education in a survey it made several years ago on Business Education at the Collegiate Level. Of the 1000 questionnaires sent out 471 complete replies were received and 40 were returned because of unsatisfactory addresses. Of the 471 replies received 424 or 90% listed principles of accountancy, 394 or 84% listed written English, and 391 or 83% listed principles of economics as of primary importance. Another substantiation of the point of view of the alumni relative to the first five subjects in importance is the fact that they were also the ones recognized as the most indispensable. Not even one of the 471 respondents marked principles of accountancy or business law as of doubtful or no value and only one each marked principles of economics, written English and oral English in that category.